Suporte de nanopartículas de metais de transição para desenvolvimento de materiais antimicrobianos - Libero, Laura Ordonho (Universidade Federal de São Carlos, 2024)
The control of diseases caused by highly contagious microorganisms is a current global challenge, where mass vaccination has shown a positive impact but faces limitations in terms of development and availability. During the COVID-19 pandemic, the need for rapid interventions, such as lockdowns and mask usage, highlighted the importance of effective decontamination strategies. Recent studies indicate that metal nanoparticles and transition metal oxides can be a promising solution, with physicochemical properties that enable the effective elimination of pathogens. However, to ensure better applicability, the use of biopolymer chitosan is of extreme interest, as it presents biocompatibility and antimicrobial activity. Therefore, this work aims to present synthesis methods related to nanoparticles, the mechanisms associated with biocidal action, as well as the possible applications of these as surface coatings, food packaging, among others.
Support of transition metal nanoparticles for the development of antimicrobial materials
Keywords: Nanopartículas; Quitosana; Materiais biocida; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::FISICO QUIMICA INORGANICA